A fatigue crack growth rate testing method and device for additively manufactured metal

By using the identification load spectrum and nine-point average method to measure the crack leading edge coordinates in additive manufacturing metal materials, combined with the finite element method to verify the stress intensity factor calculation, the fatigue crack propagation rate is obtained by using the separating method, which solves the difficulty in the prior art It effectively reflects the complex impact of microstructure and defects on fatigue crack propagation in additive manufacturing metal materials, and achieves high-precision and real fatigue crack propagation rate testing.

CN118329662BActive Publication Date: 2025-02-14BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410480986.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-02-14
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reflect the complex behavior and mechanism of microstructure and defects in additively manufactured metal materials on fatigue crack propagation, resulting in a lack of intuitive observation and high-precision measurement of fatigue crack propagation rate testing methods.

Method used

The fatigue crack propagation test was performed using the marking load spectrum, and the crack leading edge coordinates in the fracture image were measured by the nine-point averaging method, the stress intensity factor was calculated, and the calculation method was verified by the finite element method, and the fatigue crack propagation rate was finally obtained by the separating method.

Benefits of technology

Direct observation of the interaction behavior of microstructure and defects and cracks in additive manufacturing metal materials is achieved, and true and reliable fatigue crack propagation rate data are obtained, simplifying the calculation process and reducing economic and time costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118329662B_ABST
    Figure CN118329662B_ABST
Patent Text Reader

Abstract

The present invention discloses a fatigue crack growth rate test method and device for additively manufactured metals, the method comprising: preparing a compact tensile test piece of additively manufactured metal materials; placing the compact tensile test piece in a fatigue test device, carrying out a fatigue crack growth test using an identification load spectrum, and photographing a fracture image of the entire crack growth process; based on the fracture image, measuring the crack front coordinates using a nine-point average method to obtain the crack size; substituting the crack size into a stress intensity factor expression to obtain the stress intensity factor of the crack front and its amplitude; using a finite element method to verify and calculate the stress intensity factor; based on the relationship between crack length and cycle number, using a secant method to determine the fatigue crack growth rate. The present invention takes into account the complex influence behavior and mechanism of microstructure and defects on crack growth in additively manufactured metals, and systematically establishes a fatigue crack growth rate test method based on an identification load method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fatigue crack growth rate testing, and in particular relates to a fatigue crack growth rate testing method and a device for additively manufactured metal. Background Art

[0002] Additive manufacturing (AM) is the most popular advanced manufacturing technology in recent years. It is a process of printing materials layer by layer and connecting them to form entities. It has been applied in large integrated aircraft structures such as reinforced frames, frame-beam structures, wing beams, and landing gears. However, the overall structure has poor accessibility, inspectability, and repairability. Therefore, it is particularly important to design, analyze, and evaluate the damage tolerance characteristics of the structure and study the fatigue crack growth performance of the material. However, the unique liquid-solid phase transition and layer-by-layer stacking process of AM materials form anisotropic characteristics such as large-sized columnar crystals and their internal textured microstructures, and introduce fatigue sensitive factors such as defects and residual stresses, resulting in complex fatigue crack growth behavior. Therefore, it is necessary to develop a fatigue crack growth rate test method to reflect the interaction between AM material characteristics and cracks.

[0003] The ASTM E647 standard recommends three methods for crack size measurement, including visual method, flexibility method and potential difference method. The visual method test process uses a mobile microscope to measure the crack length in real time, which is greatly affected by equipment, test personnel, etc., and the surface crack is difficult to reflect the three-dimensional characteristics of the crack extension front. The flexibility method and the potential difference method are widely used to infer the crack length based on the measured data through the relationship between flexibility and voltage and crack length, respectively. However, these two methods are based on the averaging method of far-field measurement, lacking the intuitive observation of the interaction between AM characteristics such as microstructure and defects and cracks. There are also studies that use synchrotron radiation X-ray micro-computed tomography to characterize the crack extension performance of traditional / AM metal materials and observe three-dimensional crack extension behavior. However, this method is difficult to directly observe the influence of microstructure on crack extension, has high requirements on the accuracy of test equipment, complex data processing, high test and time costs, and is difficult to apply in large-scale engineering.

[0004] The identification load method is a test technology that can intuitively display complex crack growth behavior. It has application prospects in the study of crack growth in AM metal materials / structures with uneven grain arrangement, significant grain directionality, and random defect distribution. However, the existing identification load method does not consider the complex influence behavior and mechanism of microstructure and defects on crack growth in AM metals, and does not establish a systematic fatigue crack growth rate test method. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a fatigue crack growth rate testing method for additively manufactured metals to solve the problems existing in the above prior art.

[0006] To achieve the above object, the present invention provides a fatigue crack growth rate testing method for additively manufactured metals, comprising:

[0007] Preparation of compact tensile specimens of additively manufactured metal materials;

[0008] The compact tensile test piece is placed in a fatigue test device, a fatigue crack growth test is carried out using a marked load spectrum, and a fracture image of the entire crack growth process is obtained by taking pictures;

[0009] Based on the fracture image, the crack front coordinates are measured by a nine-point average method to obtain the crack size;

[0010] Substituting the crack size into the stress intensity factor expression, the stress intensity factor and its amplitude at the crack front are obtained;

[0011] Using the finite element method, verifying and calculating the stress intensity factor, and determining a calculation method of the stress intensity factor;

[0012] Based on the relationship between the crack length and the number of cycles, the fatigue crack growth rate is obtained by using the secant method, wherein the fatigue crack growth rate has a corresponding relationship with the stress intensity factor.

[0013] Preferably, the process of measuring the crack front coordinates by the nine-point averaging method includes:

[0014] The fracture image is imported into the image data extraction software, and the fracture image is divided by the nine-point average method to obtain a plurality of dividing horizontal lines;

[0015] Based on the point capture method, the intersection of the dividing horizontal line and each identification line in the identification load spectrum is obtained, and based on the coordinates of the intersection points, a coordinate data set is obtained;

[0016] Based on the coordinate data set, the crack length corresponding to each identification line is calculated using the crack length formula.

[0017] Preferably, the crack length formula is:

[0018]

[0019] Among them, a j Add the distance from the nail hole to the front edge of the notch to each x coordinate, j = 1,…,9.

[0020] Preferably, the stress intensity factor expression is:

[0021]

[0022] Among them, P maxis the maximum load of the reference load, B is the specimen thickness, W is the specimen width, α=a / W, α≥0.2;

[0023] The calculation process of the stress intensity factor amplitude ΔK is as follows: first replace α in the above formula with the average value of the sizes of two adjacent cracks Divide by W to calculate a K value, and then multiply (1-R) ​​by the K value to calculate ΔK, where R is the stress ratio of the base load.

[0024] Preferably, the process of verifying and calculating the stress intensity factor using the finite element method includes:

[0025] Based on the joint simulation of ABAQUS and FRANC3D, static calculations were performed on the cracked body of additively manufactured metal materials, and a first calculation result using finite element method and a second calculation result using stress intensity factor expression were obtained. The first calculation result was similar to the second calculation result, and the verification was passed.

[0026] Preferably, the process of obtaining the fatigue crack growth rate using the secant method is:

[0027]

[0028] Among them, a i and N i are the length a of the i-th crack and the number of cycles N, and da / dN is the fatigue crack growth rate.

[0029] The present invention also discloses a computing device, which is used to execute the fatigue crack growth rate testing method.

[0030] Compared with the prior art, the present invention has the following advantages and technical effects:

[0031] The present invention provides a fatigue crack growth rate test method for additively manufactured metals. First, a compact tensile test piece of additively manufactured metal materials is prepared; the compact tensile test piece is placed in a fatigue test device, a fatigue crack growth test is carried out using a marked load spectrum, and a fracture image of the entire crack growth process is captured; based on the fracture image, the crack front coordinates are measured using a nine-point average method to obtain the crack size; the crack size is substituted into a stress intensity factor expression to obtain the stress intensity factor of the crack front and its amplitude; a finite element method is used to verify and calculate the stress intensity factor to determine a calculation method for the stress intensity factor; based on the relationship between the crack length and the number of cycles, a secant method is used to obtain the fatigue crack growth rate, wherein the fatigue crack growth rate corresponds to the stress intensity factor.

[0032] The present invention takes into account the complex influence behavior and mechanism of microstructure and defects in AM metal on fatigue crack propagation, and then establishes a fatigue crack propagation rate test method for additively manufactured metal based on the real crack front morphology. Compared with the visual method for measuring surface cracks and the compliance method for far-field measurement, it can directly observe the interaction behavior between AM microstructure and defects and cracks, and the measured crack propagation rate is real and reliable. The present invention uses the finite element method to calculate the stress intensity factor with a complex crack front, and proposes that the stress intensity factor expression can be used to conservatively measure the stress intensity factor of the crack front, which simplifies the calculation process, so the operation process is simple and easy to apply.

[0033] The present invention only needs to reasonably determine the parameters in the identification load spectrum to obtain a clearly visible identification line in the fracture, and an optical microscope can be used to determine the crack length. Compared with mature methods such as the visual method and the flexibility method, the economic cost of building crack observation equipment and the time cost of complex data processing are saved. The method has strong generalization ability and can be promoted and applied to crack growth rate tests in other special metal materials and special environments, and is not limited to the research object of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0035] Figure 1 This is a flow chart of a fatigue crack growth rate testing method according to an embodiment of the present invention;

[0036] Figure 2 Schematic diagram of a compact tensile specimen according to an embodiment of the present invention, (a) schematic diagram of LMD forming process and sampling of compact tensile specimen; (b) drawing of compact tensile specimen;

[0037] Figure 3 A schematic diagram of a load spectrum including two reference loads and a marking load applied in a crack extension test according to an embodiment of the present invention;

[0038] Figure 4 The fracture pictures of the crack extension test obtained by using an optical microscope according to the embodiment of the present invention, (a) is the X-1 specimen; (b) is the X-2 specimen; (c) is the Y-1 specimen; (d) is the Y-2 specimen; (e) is the Z-1 specimen; (f) is the Z-2 specimen;

[0039] Figure 5 Schematic diagram of a method for determining crack front coordinates based on a nine-point average method according to an embodiment of the present invention, taking the fracture surface of a X-1 specimen as an example;

[0040] Figure 6Statistical graphs of five nanoindentation tests on two microstructures in three columnar crystals of the embodiment of the present invention, (a) is the XY sample; (b) is the XZ sample; (c) is the YZ sample;

[0041] Figure 7 The finite element model and calculation result diagram of the C(T) specimen of the embodiment of the present invention, (a) is the geometry and boundary conditions; (b) is the mesh division; (c) is the stress cloud diagram in the Y direction;

[0042] Figure 8 Schematic diagram of meshing results of a cracked structure according to an embodiment of the present invention, (a) is a crack with actual morphology; (b) is a crack with average size;

[0043] Fig. 9 Schematic diagram of static calculation results of a crack structure with an average size of 28.41 mm according to an embodiment of the present invention, (a) is a stress cloud diagram in the Z direction; (b) is a strain cloud diagram in the Z direction; (c) is a relationship diagram between the stress and strain in the Z direction extracted along the crack front path and the z coordinate;

[0044] Fig.10 Schematic diagrams of four finite element calculation examples of embodiments of the present invention, wherein a crack with actual morphology / crack with average size is inserted into the finite element model, Poisson's ratio ν=0.34 / ν=0, and the relationship between the calculated stress intensity factor K and the z coordinate, as well as a comparison diagram thereof with the K-expression;

[0045] Fig.11 The crack front stress intensity factor K is obtained by using K-expression and finite element method for two crack extension specimens in three forming directions in the embodiment of the present invention. Exp With K FEM Relationship diagram, (a) is X-1 specimen; (b) is X-2 specimen; (c) is Y-1 specimen; (d) is Y-2 specimen; (e) is Z-1 specimen; (f) is Z-2 specimen;

[0046] Fig.12 This is a comparison chart of crack growth performance obtained by three methods, namely, visual method, compliance method and marking load method, for two fatigue crack growth specimens in three forming directions according to an embodiment of the present invention, wherein schematic diagrams of aN curves are as follows: (a) for the specimen in the X direction; (b) for the specimen in the Y direction; (c) for the specimen in the Z direction; da / dN-ΔK curves: (d) for the specimen in the X direction; (e) for the specimen in the Y direction; and (f) for the specimen in the Z direction. DETAILED DESCRIPTION

[0047] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0048] It should be noted that the steps shown in the flowcharts of the accompanying drawings can be executed in a computer system such as a set of computer executable instructions, and that, although a logical order is shown in the flowcharts, in some cases, the steps shown or described can be executed in an order different from that shown here.

[0049] Embodiment 1

[0050] like Figure 1 As shown, in this embodiment, a fatigue crack growth rate test method for additively manufactured metal is provided, comprising:

[0051] S1, preparation of compact tensile specimens of additively manufactured metal materials;

[0052] Specifically, the specimens were prepared by using the mature laser metal deposition (LMD) process to prepare the TC4 block, which was placed in a heat treatment furnace for annealing at 600°C for 4 hours, and then two compact tensile specimens in each of the three forming directions of X / Y / Z were sampled from the block using electrical discharge machining and CNC grinding. The schematic diagram of the LMD TC4 block forming process and the sampling of compact tensile specimens is shown in Figure 2 (a), the specimen drawing of the compact tensile specimen is shown in Figure 2 (b) The width of the compact tensile specimen is W = 60 mm and the thickness is B = 13 mm to reflect the difference in the number of columnar crystals arranged in different directions.

[0053] S2, placing the compact tensile specimen in a fatigue test device, carrying out a fatigue crack growth test using a marked load spectrum and photographing it, obtaining a fracture image of the entire crack growth process;

[0054] Specifically, fatigue crack growth tests are carried out based on the basic methods and principles of the constant force amplitude test procedure with crack growth rates higher than 10 -8 Crack extension test of m / cycle. In order to compare the test effects of the identification load method, visual method and compliance method on fatigue crack growth rate, these three methods are used to measure the crack length at the same time. A pair of U-shaped clamps are connected to the C(T) specimen through pins, and then clamped on the Instron8872-25kN hydraulic servo fatigue testing machine. A CCD camera with a ring light is placed on a stepper. The horizontal moving track of the stepper is parallel to the surface of the specimen. The horizontal stepping distance is controlled by a computer to achieve real-time visual measurement of the surface crack length with an accuracy of 0.01mm. The COD gauge is clamped at the notch of the specimen to measure the crack opening displacement, and the compliance method is used to measure the crack length using the method in the standard. The test load adopts Figure 3 The load spectrum shown in the figure is applied. A load block of the load spectrum contains three load cycles: (1) high-frequency reference load: maximum load P maxAccording to the experimental results, the stress ratio is 0.06, the sine wave frequency is 20Hz, and the number of cycles is N. bl-h (According to the principle of making the crack increment interval as uniform as possible, the number of cycles is adjusted in real time); (2) Low-frequency reference load: Maximum load P max , stress ratio 0.06, sine wave, frequency 1Hz, number of cycles N bl-l Set to 100 cycles, the crack length is measured by visual inspection within this load cycle, and the crack length within this load cycle is obtained based on the compliance method; (3) Marking load: P max Same as the benchmark load, stress ratio 0.7, sine wave, frequency 25Hz, number of cycles N ml With N bl-h Equal. bl-h With N bl-l The sum of is the number of cycles N corresponding to the crack length.

[0055] S3, based on the fracture image, measuring the crack front coordinates by a nine-point average method to obtain the crack size;

[0056] Specifically, the crack size was measured, and after the test, a macroscopic fracture picture was taken using an optical microscope to obtain information about the entire crack extension process and observe the morphology of the identification line. Figure 4 As shown in the figure, the marking load method leaves a clear and moderately spaced marking line feature in the fracture, which forms an optical difference with the surrounding area. Referring to the ISO 12135 standard for the nine-point average method of the crack front in the quasi-static fracture toughness test fracture, a method for interpreting the fatigue crack front coordinates based on the nine-point average method was established, and the X-1 fracture was used as an example to explain it in detail. See the schematic diagram. Figure 5 First, the fracture picture taken by optical microscope is imported into Getdata software (version: 2.20), and a rectangular coordinate system is established with the lower surface of the specimen shown by the green line as the X-axis and the front edge of the notch shown by the blue line as the Y-axis. The minimum value of the x and y coordinates is set to 0, and the maximum value is the specimen width W and the specimen thickness B respectively; then, a red horizontal line running through the width direction is drawn at 0.01B from the upper and lower surfaces of the specimen, and then a red horizontal line is drawn in 8 equal parts in the 0.98B thickness interval. These horizontal lines are named 1-9 horizontal lines from bottom to top; then, the point capture mode is used to capture the intersection of horizontal lines 1-9 and each identification line, and lines of the same color are used to connect to represent the shape of the identification line, and a coordinate data set of 9 points on each identification line is established, and each x coordinate is added to the distance from the nail hole to the front edge of the notch (the present invention is 12mm) to obtain a j (j=1,…,9); finally, the crack length a corresponding to each identification line is calculated using formula (1).

[0057]

[0058] S4, substitute the crack size into the stress intensity factor expression to obtain the stress intensity factor and its amplitude at the crack front;

[0059] Specifically, to determine the stress intensity factor and its amplitude, in view of the microstructural characteristics of LMD TC4, which has coarse columnar crystals, common α-bundles at the columnar grain boundaries, and basket-like structures inside the columnar crystals, it is necessary to study whether the material has inhomogeneity in micromechanical properties, and then explore the feasibility of using continuum mechanics theory for finite element modeling and calculation of stress intensity factors. Therefore, the metallographic sampling method was used to sample rectangular samples with parallel upper and lower surfaces from the three characteristic planes XY / XZ / YZ of the raw material, and the α-bundles and basket-like structures in the three columnar crystals were selected respectively. Five points with a spacing of 10μm were selected for nanoindentation tests to obtain the load-displacement curves, and the Oliver-Pharr method was used to calculate the reduced modulus E and nanohardness H. Figure 6 The results of nanoindentation are shown. The x-axis label is defined as "Sample Name - Microstructure Type - Columnar Crystal Number". "Col / Bas" are the abbreviations of α-bundles and basketweave structures, respectively. Comparing the micromechanical properties of the two microstructures of the same grain, it can be found that the modulus of almost all α-bundles is higher than that of the basketweave structure, but the average deviation is less than 2%, and there is no regularity in the size relationship of hardness. Comparing the micromechanical properties of different grains, except that the hardness of grain 1 in the XZ sample is higher than that of the other two grains, there is no significant difference in the two mechanical properties. This shows that the mechanical properties of LMD TC4 in a single direction are slightly different between grains and within grains, and it can be considered that the mechanical properties are uniform, and then the finite element modeling and analysis can be carried out according to the uniformity assumption.

[0060] For compact tensile specimens that are in plane strain throughout the thickness, the stress intensity factor expression (K-expression) at the crack front can be calculated using formula (2). max is the maximum load of the reference load, B is the specimen thickness, W is the specimen width, α=a / W, α≥0.2. The calculation process of the stress intensity factor amplitude ΔK is: first replace α in the above formula with the average value of the sizes of two adjacent cracks Divide by W to calculate a K value, and then multiply (1-R) ​​by the K value to calculate ΔK, where R is the stress ratio of the reference load. It needs to be verified whether the stress intensity factor of the complex crack front caused by coarse columnar crystals in LMD TC4 can also be calculated using this formula.

[0061]

[0062] S5, using a finite element method to verify and calculate the stress intensity factor to determine a calculation method for the stress intensity factor.

[0063] Specifically, this embodiment carries out static calculation on the cracked body based on ABAQUS+FRANC3D joint simulation, and the calculation process is divided into the following three steps.

[0064] S51, finite element modeling based on ABAQUS. A three-dimensional model of the C(T) specimen is established in ABAQUS, such as Figure 7 As shown. The material properties are given as isotropic, linear elastic, elastic modulus E = 120GPa, Poisson's ratio ν = 0.34, and the cross-sectional properties are solid and continuous. Reference points RP-1 and RP-2 are added at the center of the upper and lower nail holes, and coupled with the motion of the inner wall of the nail hole. The displacement boundary condition at RP-1 is U1 = U3 = UR1 = UR2 = 0, the load condition is a concentrated force of 7kN in the Y direction, and the displacement boundary condition at RP-2 is U1 = U2 = U3 = UR1 = UR2 = 0. Figure 7 (b) is the mesh division. Since the subsequent static calculation of the cracked structure in FRANC3D requires further mesh refinement, a coarser mesh can be used in the global model. In this example, a cell set in the 2.5mm height area of ​​the notch front edge is established to facilitate the division of the local model. The area is divided using a 0.5mm encrypted grid size. The grid size of other areas is 1mm, the cell type is C3D8R, and the number of grids is 104949. After static calculation, the stress cloud diagram in the Y direction is shown in Figure 7 (c) The shape of the plastic zone shows the typical characteristics of the plane strain state. The maximum stress of 275.3 MPa appears at the tip of the notch, and the material has not yet entered the local yield stage.

[0065] S52, finite element modeling of cracked body based on FRANC3D. The modeling process of ABAQUS is written into .inp file, imported into FRANC3D, and the global and local models are divided. Finite element analysis of the local model can improve the computational efficiency. In this model, a user-defined crack is selected. There are two types of coordinate points on the crack, one is the crack tip vertex and the other is the non-crack tip vertex, as shown in Table 1. The crack tip vertex includes the crack front edge coordinates obtained based on the nine-point average method in (3) and the external points set to facilitate the division of the crack grid. This study takes the 16th identification line in the X-1 fracture as an example. The coordinates obtained by the nine-point method on the identification line are shown in No. 2-10 in Table 1. The coordinates of the external points are the coordinates of the intersection of the identification line and the surface translated 0.1mm in the Y direction, see No. 1 and 11. The coordinates of the non-crack tip vertex are x coordinates 0, and the y coordinates are consistent with the crack tip vertex coordinates. Input these vertex coordinates into the software to form the outer contour of the crack, and then perform mesh division. The mesh division diagram of the crack structure with actual morphology is shown in Figure 8(a). In addition, the average crack length of 28.41 mm calculated according to formula (2) is used as the x-coordinate of all crack tip vertices, and the coordinates of non-crack tip vertices remain unchanged. The same method is used to obtain the mesh division results of the crack structure with average size, see Figure 8 (b).

[0066] Table 1

[0067]

[0068] S53, static calculation of cracked body based on ABAQUS+FRANC3D. Fig. 9 The finite element method (FEM) calculation results of a crack structure with an average size of 28.41 mm are given. Figures (a) and (b) are the Z-direction stress and strain cloud maps, respectively. The Z-direction stress and strain on the path are extracted with the crack front as the path, and they are plotted in Figure (c) together with the z coordinate on the path. It can be seen that within a small range on the specimen surface, the Z-direction stress approaches 0 and the strain absolute value is the highest, indicating that this area is approximately in a plane stress state, while the Z-direction strain in the internal area approaches 0, the stress value cannot be ignored, and it is approximately in a plane strain state. In order to simulate the full-thickness material in an ideal plane strain state, the Poisson's ratio ν=0 is taken, and two examples of cracked structures are also set as a comparison with the two examples with the Poisson's ratio ν=0.34.

[0069] The M integral is used to solve the stress intensity factor of the crack front of the four examples. The relationship between the stress intensity factor K and the z coordinate is shown in Fig.10. In addition, the stress intensity factor of the crack is calculated using the K-expression shown in formula (2), and is plotted in the figure with a purple horizontal line. For the four finite element calculation results, K is integrated along the path and divided by the path length to obtain the average value of K, which is listed in Table 2 together with the solution of the K-expression, and their relative deviations from the solution of the K-expression are given. It can be seen that under the same ν, the distribution of K is affected by the crack morphology, but the K mean is similar, indicating that it is feasible to use the nine-point average method to average the crack size. In addition, the two finite element calculation results of ν = 0.34 are more than 5% higher than the solution of the K-expression, and ν = 0 is very close to the solution of the K-expression. Among them, the distribution and value of the stress intensity factor of the crack with average size are the closest to the solution of the K-expression, indicating that the K-expression can give a high-precision solution for the ideal plane strain state, but there is a difference with the actual stress state. However, considering the problem of calculation amount, it is not realistic to calculate the real K for each crack. Since the true K mean value is larger than the solution of the K-expression, the true da / dN-ΔK curve is below the curve of the K-expression, the truly evaluated crack growth resistance is greater and the crack growth life is longer. Therefore, the use of the K-expression can more conservatively evaluate the crack growth performance of the material and greatly reduce the amount of calculation.

[0070] Table 2

[0071]

[0072] The above method was used to interpret the identification lines in the fracture of two specimens in each of the three forming directions based on the nine-point average method to form a crack front coordinate data set. With the help of the Python secondary development interface of FRANC3D, a Python program for batch calculation of stress intensity factors was written. Based on the FEM model of the average size crack and ν = 0, the crack front stress intensity factor K based on the finite element method was obtained. FEM , and the solution of the K-expression is calculated as the crack front stress intensity factor K determined by the experimental method Exp , together with K FEM Drawn on Fig.11 , and K is inserted in the figure Exp =K FEM The straight line is convenient for comparing the size relationship between the two. Overall, K Exp With K FEM The values ​​are very close. In the low K region, K FEM Slightly higher than K Exp , but the error is within 5%, which is attributed to the greater influence of the pin hole on the stress intensity factor and crack opening displacement when the crack is shorter.

[0073] Therefore, although the specimen has a small range of plane stress state, the K-expression can be used to estimate the stress intensity factor more conservatively, which is more convenient than using the finite element method to calculate the stress intensity factor of the real crack front. Based on this consideration, the method recommended in the standard can be used to calculate the stress intensity factor amplitude based on the relationship between K and ΔK.

[0074] S6. Based on the relationship between the crack length and the number of cycles, a secant method is used to obtain a fatigue crack growth rate, wherein the fatigue crack growth rate corresponds to the stress intensity factor.

[0075] Specifically, the fatigue crack growth rate da / dN is determined by using the secant method recommended in the standard. The crack length a and the number of cycles N are substituted into formula (3) to calculate da / dN.

[0076]

[0077] In order to compare the test effects of the two mature methods of the marking load method, the visual method and the compliance method on the fatigue crack growth rate, the crack size a and the corresponding cycle number N are plotted on Fig.12 (a)-(c). Then the fatigue crack growth rate da / dN is calculated using the secant method recommended in the standard, i.e., equation (3), and plotted against the stress intensity factor amplitude ΔK. Fig.12(d)-(f). From the aN curve, it can be seen that under different forming directions and test methods, with the increase of N, the trend of a from slow increase to rapid increase is similar. Among the test results of these 6 specimens, the a obtained by the X-2 specimen using the identification load method is significantly higher at a lower N, indicating that the direct reading of the surface crack by the visual method produces a large error when a is small, which in turn leads to the calibration deviation of the elastic modulus of the flexibility method, causing the aN curve to deviate from the actual. Comparing the da / dN-ΔK curves obtained by the identification load method and the other two methods, it can be found that the data overlaps well, but the identification load method has good regularity, and there are rate fluctuations in local areas, indicating that this method can truly reflect the local fluctuation characteristics of the fatigue crack growth rate related to the microstructure. The visual method has a sudden decrease in fatigue crack growth rate in many places. After observing the identification lines in the fracture corresponding to these data, it is found that the surface crack length is not significantly lower than the internal crack length, indicating that the visual method misreads the surface crack. The data of the compliance method has the smallest fluctuation, which is attributed to the fact that this method measures the stress state far away from the crack tip and ignores the complex stress state at the crack tip. The coupling effect between the microstructure and stress state and the crack tip is not fully reflected in the fatigue crack growth rate test results. In summary, the identification load method is a fatigue crack growth rate test method based on the actual crack size and complex crack front morphology. Compared with the visual method and the compliance method, it can directly observe the interaction behavior between the AM microstructure and defects and cracks, and the measured fatigue crack growth rate is real and reliable. In addition, the test process of this method is simple, highly operational, and is not limited by the size of the material / structure. It only requires applicable fatigue test equipment, a reasonable identification load spectrum, and ordinary fracture observation equipment, which saves the economic cost of setting up crack observation equipment and the time cost of complex data processing. It has broad application prospects in the damage tolerance assessment of complex structures.

[0078] Beneficial effects of this embodiment:

[0079] This embodiment takes into account the complex influence behavior and mechanism of microstructure and defects in AM metal on fatigue crack growth, and then establishes a fatigue crack growth rate test method for additively manufactured metal based on the real crack front morphology. Compared with the visual method for measuring surface cracks and the compliance method for far-field measurement, the technical advantages are significant. The present invention uses the finite element method to calculate the stress intensity factor with a complex crack front, and proposes that the stress intensity factor expression can be used to conservatively measure the stress intensity factor, which simplifies the calculation process, so the operation process is simple and easy to apply.

[0080] This embodiment aims at the characteristics of these AM material characteristics that affect fatigue crack growth behavior, and establishes a systematic crack growth rate test method. It only needs to reasonably determine the parameters in the identification load spectrum to obtain a clearly visible identification line in the fracture, and use an optical microscope to determine the crack length. Compared with mature methods such as the visual method and the flexibility method, no other testing equipment is required, so the economic benefits are outstanding. This method has a strong generalization ability and can be promoted and applied to fatigue crack growth rate tests in other special metal materials and special environments, and is not limited to the research object of the present invention.

[0081] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A fatigue crack growth rate test method for additively manufactured metals, characterized in that: The following steps are involved: Preparation of compact tensile specimens of additively manufactured metal materials; The compact tensile test piece is placed in a fatigue test device, a fatigue crack growth test is carried out using a marked load spectrum, and a fracture image of the entire crack growth process is obtained by taking pictures; Based on the fracture image, the crack front coordinates are measured by a nine-point average method to obtain the relationship between the crack length and the cycle number; Substituting the crack length into the stress intensity factor expression, the stress intensity factor and its amplitude at the crack front are obtained; The stress intensity factor expression is: Among them, P max is the maximum load of the reference load, B is the specimen thickness, W is the specimen width, α=a / W, α≥0.2; The calculation process of the stress intensity factor amplitude ΔK is as follows: first replace α in the above formula with the average length of two adjacent cracks Divide by W to calculate a K value, and then multiply (1-R) ​​by the K value to calculate ΔK, where R is the stress ratio of the base load; Using the finite element method, verifying and calculating the stress intensity factor, and determining a calculation method of the stress intensity factor; Based on the relationship between the crack length and the number of cycles, the fatigue crack growth rate is obtained by using the secant method, wherein the fatigue crack growth rate has a corresponding relationship with the stress intensity factor.

2. The fatigue crack growth rate testing method of additively manufactured metal according to claim 1, characterized in that: The process of measuring the crack front coordinates by the nine-point averaging method includes: The fracture image is imported into the image data extraction software, and the fracture image is divided by the nine-point average method to obtain a plurality of dividing horizontal lines; Based on the point capture method, the intersection of the dividing horizontal line and each identification line in the identification load spectrum is obtained, and based on the coordinates of the intersection points, a coordinate data set is obtained; Based on the coordinate data set, the crack length corresponding to each identification line is obtained by using a crack length calculation formula.

3. The fatigue crack growth rate testing method of additively manufactured metal according to claim 2, characterized in that: The crack length calculation formula is: Among them, a j Add the distance from the nail hole to the front edge of the notch to each x coordinate, j = 1,…,9.

4. The fatigue crack growth rate testing method of additively manufactured metal according to claim 1, characterized in that: The process of verifying and calculating the stress intensity factor using the finite element method includes: Based on the joint simulation of ABAQUS and FRANC3D, static calculations were performed on the cracked body of additively manufactured metal materials, and a first calculation result using finite element method and a second calculation result using stress intensity factor expression were obtained. The first calculation result was similar to the second calculation result, and the verification was passed.

5. The fatigue crack growth rate testing method of additively manufactured metal according to claim 1, characterized in that: The process of obtaining fatigue crack growth rate using the secant method: Among them, a i and N i are the length a of the i-th crack and the number of cycles N, and da / dN is the fatigue crack growth rate.

6. A computing device, characterized in that: The computing device is used to execute a fatigue crack growth rate testing method as described in any one of claims 1-5.

Citation Information

Patent Citations

  • Fatigue crack propagation rate testing method of steel box girder

    CN105352800A

  • Bidirectional fatigue crack expansion rate testing method and testing system

    CN106568662A